2018
DOI: 10.1371/journal.pntd.0006661
|View full text |Cite
|
Sign up to set email alerts
|

Heme crystallization in a Chagas disease vector acts as a redox-protective mechanism to allow insect reproduction and parasite infection

Abstract: Heme crystallization as hemozoin represents the dominant mechanism of heme disposal in blood feeding triatomine insect vectors of the Chagas disease. The absence of drugs or vaccine for the Chagas disease causative agent, the parasite Trypanosoma cruzi, makes the control of vector population the best available strategy to limit disease spread. Although heme and redox homeostasis regulation is critical for both triatomine insects and T. cruzi, the physiological relevance of hemozoin for these organisms remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Notably, the AMG had previously been described as a compartment in which there was only absorption of water, erythrocyte hemolysis, hemoglobin crystallization, and hemozoin formation ( Garcia et al, 2007 ; Ferreira et al, 2018 ). It has been hypothesized that the high levels of family A1 transcripts in the AMG might be caused by their synthesis as pro-enzymes, which would then be activated in the PMG ( Ribeiro et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the AMG had previously been described as a compartment in which there was only absorption of water, erythrocyte hemolysis, hemoglobin crystallization, and hemozoin formation ( Garcia et al, 2007 ; Ferreira et al, 2018 ). It has been hypothesized that the high levels of family A1 transcripts in the AMG might be caused by their synthesis as pro-enzymes, which would then be activated in the PMG ( Ribeiro et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic proteins located in their surface and sugar residues present in perimicrovillar membrane glycoproteins appear to be necessary for this interaction ( Zingales et al, 1982 ; Golgher et al, 1993 ; Pereira-Chioccola et al, 2000 ; Alves et al, 2007 ; Nogueira et al, 2007 ). In R. prolixus , it has been shown that another function of the perimicrovillar membranes is the promotion of the aggregation of heme molecules, forming nucleation sites that convert heme into hemozoin crystals and hence preventing heme toxicity toward both the host and the parasite, that consequently creates a favorable environment for pathogen growth ( Oliveira et al, 2000 ; Stiebler et al, 2014 ; Ferreira et al, 2018 ).…”
Section: Peritrophic Matrixmentioning
confidence: 99%
“…An oxidant environment must stimulate epimastigote proliferation and an antioxidant environment promotes metacyclogenesis (Nogueira et al, 2015). Ferreira et al (2018) suggested that heme undergoes a crystallization process in the gut of the insect that is both a protective process to T. cruzi and the triatomine.…”
Section: The Incomplete Heme Synthesis In Trypanosomatids and The Requirement Of Hemes From Mammalsmentioning
confidence: 99%